1978
DOI: 10.1136/jnnp.41.12.1097
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological aspects of sensory conduction velocity in healthy adults. 2. Ratio between the amplitude of sensory evoked potentials at the wrist on stimulating different fingers in both hands.

Abstract: S U M M ARY The normal ratio between the amplitude of the sensory evoked potential (SEP) at the wrist on stimulating digits 1, 2, 3, and 5 was determined in 44 healthy adult subjects. The first digit had the larger amplitude, and the fifth digit the smallest SEP. The amplitude expresses the density of sensory innervation in each finger. The ratio between the amplitude of different fingers varied according to the age of the subject. The amplitude of the SEP from a digit innervated by the median nerve decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…The largest study we found included 372 newborns, infants, and children, 11,12 whereas most others had fewer than 200 patients. 7,10,[13][14][15][16][17][18][19]21,24 Very few data on establishing normal pediatric NCS values have been published in the last 15 years, although a notable study reported normal values for the femoral nerve. 22 We created comparison tables of our data vs. those of previous studies (see Tables S1-4 online).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest study we found included 372 newborns, infants, and children, 11,12 whereas most others had fewer than 200 patients. 7,10,[13][14][15][16][17][18][19]21,24 Very few data on establishing normal pediatric NCS values have been published in the last 15 years, although a notable study reported normal values for the femoral nerve. 22 We created comparison tables of our data vs. those of previous studies (see Tables S1-4 online).…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Since then, multiple studies establishing normal values in pediatric NCS have been reported. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The sample sizes in these normative studies were relatively small, especially when compared with the higher volumes seen in referral centers in recent years. Furthermore, many laboratories have reported their own pediatric reference values when discussing normal or abnormal EDx results, without a clear explanation of the methodology used to obtain these values.…”
mentioning
confidence: 99%
“…Orthodromic conduction of the sural nerve was calculated by recording the potential at the mid calf after stimulation at the ankle. More details of conduction study methods and normal values used in our laboratory for different ages have been reported (Cruz-Martinez et al, 1977a, 1978a.…”
Section: Methodsmentioning
confidence: 99%
“…Substantial slowing in conduction velocity implies demyelination of the sensory fibers, whereas axonotmesis results in reduced amplitude of compound nerve action potentials with stimulation distal to the site of lesion. Degeneration of sensory fibers occurs only with a postganglionic lesion, such as plexopathy or peripheral neuropathy [12). This fact can be used as a criterion in differentiating postganglionic from preganglionic disorders, such as syringomyelia or root avulsion.…”
Section: Types Of Neuropathic Abnormalitymentioning
confidence: 99%